TURKISH VALIDITY AND RELIABILITY STUDY OF CANCER EMPOWERMENT SCALE - Karabulutlu, Elanur Yilmaz; Turan, Gulcan Bahcecioglu; Karaman, Seda (Medicinska Naklada, 2021)
Background: The present study aims to adapt Cancer Empowerment Scale to Turkish and to test its validity and reliability. Subjects and methods: This methodological study consisted of 286 cancer patients receiving treatment. Cancer Empowerment Scale (CES) were used in this study. Results: The scale's content validity index was found as 0.96. Total Cronbach's alpha coefficient of the scale is 0.93. Cronbach's alpha coefficient is 0.92 for personal strength dimension, 0.95 for social support dimension, 0.87 for healthcare and 0.94 for community support. Item factor loads were found to range between 0.40 and 0.87 and item total correlation coefficients were found to be between 0.32 and 0.59. Confirmatory factor analysis (CFA) and exploratory factor analysis (EFA) conducted supported the 4 factor structure of the scale. CFA results showed good fit index values. Conclusions: Turkish version of Cancer Empowerment Scale is a valid and reliable measurement tool to evaluate the empowerment states of cancer patients. With this scale, it is thought that by evaluating the empowerment status of cancer patients and determining the deficiencies in this issue, it will provide supportive interventions to patients in clinical practice according to their needs.
Keywords: cancer empowerment scale reliability; Turkish adaptation; validity